Hubungan Antara Tuntutan Kerja dan Burnout dengan Motivasi Kerja Sebagai Moderator Pada Karyawan Kalangan Generasi Z di DKI Jakarta - Euvanggelia Tambuwan; Riana Sahrani (Journal on Education, 2023)
Generation Z comes at a time when the internet and information technology are developing rapidly as an attraction that replaces traditional toys in the era of the generation before them. Gen Z, who is aged, has just stepped into work, has high work motivation, their high motivation is accompanied by high performance. . This study aims to determine the role of work demands on employee burnout, especially generation Z in DKI Jakarta, with work motivation as a moderator. This research measures burnout using the burnout assessment tool by de Beek et al., job demands using the Job Demands Scale by Bekker & Demerouti, and work motivation using the Herzberg scale. This study involved 271 respondents with 117 men and 154 women. This study used a quantitative approach, data collection was carried out using a purposive sampling technique for Gen Z in DKI Jakarta. Hypothesis testing using SPSS with the Multiple Regression Analysis (MRA) method, where the results of testing the three variables obtained a value of t = 4.561 and a sig. = 0.000 > 0.05. The results of this study indicate that there is a significant correlation and relationship between work demands and burnout, as well as work motivation which can act as a moderator in the relationship between work demands and burnout.